Nanoemulsions for Parenteral Nutrition as Industrial or Laboratory Preparations - Mirković, Dušica; Ibrić, Svetlana (Vojnosanitetski pregled, 2021)
Background/Aim. The application of nanoemulsions (NE) for the parenteral nutrition represents a very important advancement that marked the Medicine and Pharmacy of the twentieth century. Over the years, the technology of the production of nanoemulsions or admixtures for the Total Parenteral Nutrition (TPN) has undergone a constant improvement. This paper representing the continuation of the previous research deals with nanoemulsions with a concentration of 20%, and which were prepared under laboratory conditions. The main emphasis was put on the possibility of detecting the potential presence of large droplets or agglomerates of droplets that could cause fatal effects. In addition, the quality assessment for the TPN admixture containing these nanoemulsions was performed. The results were compared with the results obtained by monitoring the TPN admixture prepared from the industrial emulsion (Lipofundin MCT/LCT 20%®). Methods. During the 30-day period of monitoring nanoemulsion physical-chemical characteristics, the volume diameters that define the width of the lipid droplet size distribution were determined using the laser diffraction method. The characterization of nanoemulsions also included the measurement of electrical conductivity and the peroxide number. In addition, the TPN physical and chemical characteristics were monitored for 72 hours and included: the measurement of the mean droplet diameter, the volume diameter, the distribution of the droplet size (PDI), the ζ-potential, and the pH values. Results. The obtained results were in accordance with the literature data related to the quality of parenteral nanoemulsions (the values ​​of volume diameters ranged between 50 and 490 nm, the electrical conductivity ranged from 415 to 266 µS/cm, and the peroxide value from 0.06 up to 0.12). The TPN admixtures remained stable during the testing period, even in the cases when the TPN admixtures containing either a newly formed or an industrial nanoemulsion were tested. Conclusion. All these results point to the fact that under the conditions of storage time, and at the ambient temperature, the investigated nanoemulsion characteristics do not significantly alter. If the principles of preparation and the order of mixing components are followed, the TPN admixture possessing satisfactory physical and chemical quality and stability can be obtained.